Laparoscopic radiofrequency ablation of subcapsular hepatocellular carcinomas: risk factors related to a technical failure - Ko, Seong Eun; Lee, Min Woo; Min, Ji Hye; Ahn, Soo Hyun; Rhim, Hyunchul; Kang, Tae Wook; Song, Kyoung Doo; Kim, Jong Man; Choi, Gyu Seong; Cha, Dong Ik; Lim, Hyo Keun (Surgical Endoscopy, 2022)
Background: This study aimed to evaluate the risk factors related to a technical failure after laparoscopic radiofrequency ablation (RFA) for subcapsular hepatocellular carcinomas (HCCs). Materials and methods: A total of 110 patients with 114 HCCs who underwent laparoscopic RFA for HCCs (new HCC [n = 85] and local tumor progression [LTP] [n = 29]) between January 2013 and December 2018 were included. We evaluated the incidence of technical failure on immediate post-RFA CT images. Risk factors for a technical failure after laparoscopic RFA were assessed using univariable logistic regression analyses. The cumulative LTP rate was estimated using the Kaplan–Meier method. Results: Technical failure was noted in 3.5% (4/114) of the tumors. All four tumors that showed a technical failure were cases of LTP from previous treatment and were invisible on laparoscopy. On univariate analysis, LTP lesion, invisibility of the index tumor on laparoscopy, and peri-hepatic vein location of the tumor were identified as risk factors for a technical failure. The cumulative LTP rates at 1, 3, and 5 years were estimated to be 2.8%, 4.8%, and 4.8%, respectively. Conclusions: LTP lesion, invisibility of the index tumor on laparoscopy, and peri-hepatic vein location of the tumor were identified as the risk factors for a technical failure after laparoscopic RFA.
Keywords: Carcinoma, Hepatocellular; Catheter Ablation; Humans; Laparoscopy; Liver Neoplasms; Radiofrequency Ablation; Retrospective Studies; Risk Factors; Treatment Outcome; Hepatocellular carcinoma; Laparoscopy; Liver; Local; Neoplasm recurrence; Radiofrequency ablation